Analysis of Nursing Care to mother with Post-Caesarean Pain and Lavender Aromatherapy Intervention - Winarsih, Wiwin; Yekti Widadi, Sri (CV. Literasi Publikasi Indonesia, 2024)
A Cesarean section (C-section) is a surgical procedure involving an incision into the abdominal wall and uterus to deliver a baby. This procedure disrupts tissue continuity and nerve endings, resulting in pain at the incision site post-surgery. Lavender aromatherapy is a non-pharmacological pain management technique that has been shown to alleviate pain. This study aims to evaluate the effect of lavender aromatherapy on reducing pain intensity in patients post-Cesarean section in the Marjan Bawah Room at Dr. Slamet Garut General Hospital. This descriptive study used a case study design. The Numeric Rating Scale (NRS) was used as the instrument to measure pain intensity in patients. Pain levels were assessed before and after applying lavender aromatherapy for three consecutive days. The case study revealed that the application of lavender aromatherapy significantly reduced pain intensity in post-Cesarean patients. Prior to the aromatherapy intervention, the patient's pain level was recorded as 6 (moderate pain). After three days of lavender aromatherapy, pain intensity decreased to 2 (mild pain). Lavender can effectively reduce pain intensity in post-Cesarean patients, suggesting its potential as a valuable adjunct in pain management strategies.